Randy rides alone = [Randy cabalga solo] - Fraser, Harry, 1889-1974; Parsons, Lindsley, 1905-1992; Wayne, John, 1907-1979; Lone Star Productions; Cinetel Films ([Los Angeles, CA] : Lone Star Production, 1934)
Jailed for murders he didn't commit, Randy escapes only to stumble into the den of the real murderers. Accused of murder and robbery, Randy is released from jail to the custody of Sally Rogers so he can find the real badguys. He finds their secret hideout behind a waterfall.
Originally released as a motion picture in 1934.
"A Paul Malvern Production."
John Wayne, Alberta Vaughn, George Hayes, Yakima Canutt, Earl Dwire, Arthur Artego, Tex Phelps.
Cinematographer, Archie Stout; editor, Carl Pierson; music, William Barber.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: False imprisonment -- Drama; Thieves -- Drama; Robbery -- Drama; Western films; Feature films; Internet videos; Short films; Streaming video